Cellulose Fibre-Reinforced Biofoam for Structural Applications - Obradovic J; Voutilainen M; Virtanen P; Lassila L; Fardim P (MDPI AG, 2022)
Traditionally, polymers and macromolecular components used in the foam industry are mostly derived from petroleum. The current transition to a bio-economy creates demand for the use of more renewable feedstocks. Soybean oil is a vegetable oil, composed mainly of triglycerides, that is suitable material for foam production. In this study, acrylated epoxidized soybean oil and variable amounts of cellulose fibres were used in the production of bio-based foam. The developed macroporous bio-based architectures were characterised by several techniques, including porosity measurements, nanoindentation testing, scanning electron microscopy, and thermogravimetric analysis. It was found that the introduction of cellulose fibres during the foaming process was necessary to create the three-dimensional polymer foams. Using cellulose fibres has potential as a foam stabiliser because it obstructs the drainage of liquid from the film region in these gas-oil interfaces while simultaneously acting as a reinforcing agent in the polymer foam. The resulting foams possessed a porosity of approximately 56%, and the incorporation of cellulose fibres did not affect thermal behaviour. Scanning electron micrographs showed randomly oriented pores with irregular shapes and non-uniform pore size throughout the samples.